DEVELOPMENT OPPORTUNITIES OF POLISH FARMS - Monika Juchniewicz; Łukasz Podstawka (Polityki Europejskie, Finanse i Marketing)
The main objective of the study is to identify and evaluate development opportunities among agricultural holdings in Poland according to agricultural types and economic size classes. Thestudy refers to the period between 2015 and 2019 and concerns data regarding farms run by natural persons conducting agricultural accounting within the Polish FADN. The aim of the studywas achieved by assessing the level of income from a family farm as well as accumulation and reproduction in the agricultural holdings under consideration. The research shows that there wasa differentiation in the development potential of farms run by natural persons depending on the agricultural type and economic size class. The highest average accumulation in relation to familyfarm income, as well as the highest reproduction rate, was observed in farms producing poultry.Farms with field crops, horticulture, dairy cows and pigs also had more accumulation than depreciation and these farms provided an extended reproduction of fixed assets. On the otherhand, in holdings with mixed crop and animal production, with permanent crops and specialised in grassland animal husbandry, there was a narrower reproduction of fixed assets.The analysis of agricultural holdings run by natural persons showed that the accumulation rate and the reproduction rate increased along with the economic size of agricultural holdings.Farms with an economic size of up to EUR 25 thousand SO in the studied period recorded a negative accumulation rate and reproduction rate. In the group of farms with an economic sizeof EUR 25 to 50 thousand, the reproduction rate was 1. On the other hand, in the economic size classes above EUR 50 thousand SO there was an extended reproduction.